2014
DOI: 10.1246/bcsj.20140096
|View full text |Cite
|
Sign up to set email alerts
|

Pt Nanoparticles Loaded on Reduced Graphene Oxide as an Effective Catalyst for the Direct Oxidation of 5-Hydroxymethylfurfural (HMF) to Produce 2,5-Furandicarboxylic Acid (FDCA) under Mild Conditions

Abstract: Reduced graphene oxide (RGO) is one of the most promising catalyst supports because it has faintly acidic sites together with a large amount of functional groups on its surface. In this report, we prove that, for the first time, Pt-loaded RGO (Pt/RGO) is an efficient, robust, and durable catalyst for oxidizing 5-hydroxymethylfurfural (HMF) directly to 2,5-furandicarboxylic acid (FDCA) under mild conditions. The selectivity of FDCA reaches up to 84% along with 100% HMF conversion in the presence of excess base.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…Similarly, Pt‐based catalysts have also shown higher catalytic performance for the oxidation reaction . Siankevich et al.…”
Section: Catalytic Oxidation Of Biomass‐derived Furfural and Hmf Overmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Pt‐based catalysts have also shown higher catalytic performance for the oxidation reaction . Siankevich et al.…”
Section: Catalytic Oxidation Of Biomass‐derived Furfural and Hmf Overmentioning
confidence: 99%
“…Similarly,P t-based catalysts have also shown higherc atalytic performance for the oxidation reaction. [206][207][208][209][210][211][212][213][214] Siankevich et al achieveda nefficient oxidation of HMF to FDCA over platinum nanoparticles coated with an imidazolium-based cross-linked polymeru sing oxygen as an oxidizing agent at 80 8Cu nder aqueous reaction conditions. [206] The study suggested that the counter anion of cationic polymer (chloride, BF 4 À ,P F 6 À ,b is(trifluoromethylsulfonyl)imide, hexanoate or laurateanions) affected the structure of Pt nanoparticles along with the surface electronic properties andt he catalytic activity.T he resultsinferred that bis(trifluoromethylsulfonyl)imide (weak nucleophilic anion) resulted in the highest reaction rates, which was assigned due to the weak interaction of polymer with the surface of nanoparticles and hence led to an ease access to the substrates.A nalogously,P tn anoparticles supported on functionalized carbon nanotubes (CNTs) have shown high performance towardsb ase-free aerobic oxidation of HMF to FDCA.…”
Section: Catalytic Oxidation Of Biomass-derived Furfural and Hmf Overmentioning
confidence: 99%
“…16,17 More recent studies focused on the heterogeneously catalyzed oxidation of HMF for a more sustainable process. In these studies, mainly nanoparticles of noble metals like Pt, [18][19][20][21][22][23][24] Pd, 18,[25][26][27] Ru [28][29][30][31] or Au [32][33][34][35][36] on various supports have been used for the oxidation of HMF to FDCA, often giving almost quantitative yields. For example, FDCA was produced with 96% yield after 5 h reaction time using a Au/CeO 2 catalyst at 130°C.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the most used active carbon, reduced graphene oxide (RGO) can be also used as support owing to its abundant surface functional groups, which can be used to anchor the metal nanoparticles. Niu et al studied a series of RGO supported metal nanoparticles for the oxidation of HMF at 25 • C and 1 bar O 2 , with the presence of NaOH and an O 2 flow rate of 50 mL/min [57]. The Pt/RGO catalyst showed a higher FDCA yield than Pd/RGO, Ru/RGO and Rh/RGO, and a FDCA yield of 84% could be obtained after 24 h. During the recycling experiments, an increase in HMFCA and a decrease in FDCA yield could be observed.…”
Section: Pt-based Catalystsmentioning
confidence: 99%